Tributação e liberdade religiosa: o enfrentamento dos limites no contexto de um Estado laico - Joner, Gabriel (Universidade do Vale do Rio dos Sinos, 2014)
Although state secularism figures as a placed consolidated issue in the vast majority of Western countries, the discussion involving the relationship between law and religion/religious believes are still in evidence. They also present the intrinsic feature of generates a range of great debates, at the same time, on political and legal scenario. Brazil, as a political entity, is coated facet of a democratic state, having hosted the value called "religiosity" as one of the pillars on which Brazilian society is supported. Thus, this principle is one of the fundamental rights provided by the Brazilian Federal Constitution. This state model provides that public authorities are then driven to the modification of the status quo, aiming the implementation of the rights contained in the Constitution. By accepting religious freedom as an extremely important value, the Federal Constitution prevents the state to create any kind of embarrassment to the free exercise of worship, developing on an idea, the so called “Institute of immunity”, to achieve this aim. So, if in the beginning the institute was to privilege granted to certain classes, including the clergy, now the reason of the immunity is to facilitate, through the exclusion of tax charges, the achievement of goals that must be conquered by the state itself. The objective of this research is to analyze, critically, the current context of the taxation of religious organizations in Brazil, exploring to what extent it meets the desires of a secular state and, if it has, effectively, as its aim to ensure the protection of the religious freedom of citizens.
Keywords: Direito tributário; Direitos fundamentais; Liberdade religiosa; Estado laico; Tax law; Fundamental rights; Immunity; Religious liberty; Secular state; ACCNPQ::Ciências Sociais Aplicadas::Direito